2022
DOI: 10.1186/s12885-022-09950-1
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hypokalemia can increase complications after colorectal cancer surgery: a propensity score matching analysis

Abstract: Background Whether hypokalemia can affect the short-term outcomes of CRC patients after radical surgery remains unclear. The purpose of this study was to investigate the impact of preoperative hypokalemia on the short-term outcomes for colorectal cancer (CRC) patients who underwent radical CRC surgery using propensity score matching (PSM). Methods We retrospectively enrolled consecutive CRC patients from Jan 2011 to Dec 2021 in a single-center hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…When K + < 2.5 mmol/L or K + > 6.5 mmol/L, serious cardiac damage seems inevitable and an immediate intervention is suggested. It showed that serum potassium might predict short-term outcomes after surgery and preoperative hypokalemia was an independent risk factor for overall complications [8].…”
Section: Introductionmentioning
confidence: 99%
“…When K + < 2.5 mmol/L or K + > 6.5 mmol/L, serious cardiac damage seems inevitable and an immediate intervention is suggested. It showed that serum potassium might predict short-term outcomes after surgery and preoperative hypokalemia was an independent risk factor for overall complications [8].…”
Section: Introductionmentioning
confidence: 99%